Handbook of dimensional measurement - Curtis, Mark A.; Farago, Francis T. (Industrial Press, 2014)
This edition features one completely new chapter covering The Measurement of Geometric Dimensions and Tolerances, while providing comprehensive state-of-the-art treatment of all known dimensional measurement devices and techniques. This is a unique resource organized into chapters by gauge type and function. Individual chapters move from simple to complex, from timeless measurement techniques to the most modern and innovative. As the single best and most recognized & respected reference on engineering measurement, this edition improves its position as the most comprehensive source for dimensional measurement information available. This edition includes an improved and expanded illustration program, with 50 new figures and new digital photographs. It supplements discussions with nearly 600 illustrations, line drawings and photographs. and includes improvements and innovations made by the leading manufacturers of dimensional measurement equipment, hardware, and machinery from the last edition. It describes equipment, hardware, and machinery in explicit narrative detail and brings all references to national and international standards up-to-date.